Konflik Peran Ganda Wanita Karir Saat Work From Home di Masa Pandemi Covid-19: Studi Meta analisis - Aliffia, Dhiza; Mawadah, Mawadah; Adawiyah, Rabiatul; Na'imah, Khairun; Komalasari, Shanty; Hermina, Ceria (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2022)
The Covid-19 pandemic has made significant changes to people’s lives. Including career women who work from home, feel the impact of these changes. Challenges and burdens borne by career women in the middle of public stigma about women who should be at home, doing domestic work, taking care of their husbands and children and then increasing when they have to do it together with office work at home. The purpose of this study is to reveal the dual role conflict experienced by career women when working from home during covid-19 pandemic. The method used in writing this article uses the library method. A mother who has a dual role during a pandemic finds her work responsibilities getting more difficult. The burden is in the form of the responsibility of accompanying school children from home and work responsibilities which apparently during the pandemic are increasing. Especially when children learn online. Here the role of a mother increases because she has to act as a teacher to accompany her child. This makes career women find it difficult because they are also carrying out their duties from home (WFH) at the same time. Career women often find it difficult because they have to divide their focus between work and accompanying children during online school. So that the dual role conflict experienced by career women when working from home during the Covid-19 pandemic increases because roles in work and family are carried out in the same place at the same time.